2010
DOI: 10.2215/cjn.01110210
|View full text |Cite
|
Sign up to set email alerts
|

Combined Therapy with Renin-Angiotensin System and Calcium Channel Blockers in Type 2 Diabetic Hypertensive Patients with Proteinuria

Abstract: Results: All treatment strategies effectively increased FMD and reduced proteinuria, confirming a more prone reduction with the combined therapy. These improvements were followed by significant PTX3 reductions. Valsartan alone and in combination with amlodipine achieved significant incremental raises in sTWEAK plasma levels. More importantly, the changes observed in sTWEAK (␤ ‫؍‬ 0.25, P ‫؍‬ 0.006) or PTX3 (␤ ‫؍‬ ؊0.24, P ‫؍‬ 0.007) plasma levels were independently associated with the improvement in ultrasonog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 45 publications
(44 reference statements)
2
65
1
1
Order By: Relevance
“…In this regard, short-term angiotensin-converting enzyme inhibitor treatment significantly improved endothelial function and normalized both PTX3 and urinary protein excretion in type 2 diabetic proteinuric patients (41). Also, the improvement in FMD after combined therapy with the renin-angiotensin system and calcium channel blockers was independently associated with both PTX3 and sTWEAK normalization in type 2 diabetic hypertensive patients (42). Hence, this study concluded that both PTX3 and sTWEAK levels strongly associate with the endothelial dysfunction typically observed with progressive kidney failure.…”
Section: Discussionmentioning
confidence: 89%
“…In this regard, short-term angiotensin-converting enzyme inhibitor treatment significantly improved endothelial function and normalized both PTX3 and urinary protein excretion in type 2 diabetic proteinuric patients (41). Also, the improvement in FMD after combined therapy with the renin-angiotensin system and calcium channel blockers was independently associated with both PTX3 and sTWEAK normalization in type 2 diabetic hypertensive patients (42). Hence, this study concluded that both PTX3 and sTWEAK levels strongly associate with the endothelial dysfunction typically observed with progressive kidney failure.…”
Section: Discussionmentioning
confidence: 89%
“…In dialysis patients, increased PTX3 levels strongly predicted outcome and did so independently of traditional risk factors and CRP (12)(13)(14)(15). Pharmacologically, short-term angiotensin converting enzyme inhibitor treatment significantly improved flow-mediated dilation while normalizing PTX3 and urinary protein excretion in patients with type 2 diabetes with proteinuria (27), whereas the improvement in flow-mediated dilation after treatment with antihypertensive drugs in diabetic CKD stage 1 patients with hypertension was independently associated with PTX3 normalization (28). Altogether, these results suggest that increased PTX3 may play a role in the pathogenesis of endothelial dysfunction/cardiovascular disease.…”
Section: Discussionmentioning
confidence: 91%
“…Our study reveals that PTX3 levels increases up to 15 times than the upper limit of the normal range in hypertensive patients. Yılmaz et al (18,19) investigated PTX3 levels in type 2 diabetic patients with proteinuria and demonstrated a slight increase in both hypertensive and normotensive patients. Therefore it is interesting that PTX3 levels in diabetic patients of the mentioned study is lesser increased than the levels of isolated hypertensive patients in our study.…”
Section: Discussionmentioning
confidence: 99%